The emperor's new clothes - Andersen, H. C.; Burton, Virginia Lee (Houghton Mifflin, 1949)
The emperor shows his stupidity when he walks through the city in the invisible suit two rascal tailors made for him.
Translation of: Kejserens nye klæder.
The emperor shows his stupidity when he walks through the city in the invisible suit two rascal tailors made for him.